Analysis of deep learning models on low-light pest detection - Irtiza, Md. Samin; Ahmed, Fattah; Haque, Md. Tahmidul; Tamim, Arifur Rahman; Sultana, Samia (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.